Rearrangement and expression of the alpha- and beta-chain genes of the T-cell antigen receptor in functional murine suppressor T-cell clones. - De Santis, R (1985)
Two different antigen-specific radiation leukemia virus (RadLV)-transformed suppressor T-cell clones, LH8.105 and LA41, exhibiting anti-lysozyme and anti-acetylcholine-receptor suppressor activity, respectively, have been examined for rearrangement and expression of genes encoding the alpha and beta chains of the T-cell receptor for antigen. LH8.105 cells express the T-cell-receptor polypeptides, as shown by specific immunoprecipitation. In both cell lines, potentially functional transcripts of alpha- and beta-chain genes are detected by RNA blot analysis. These suppressor T-cell clones exhibit alpha-chain gene rearrangements, deletion of both alleles of the constant-region (C) gene segment C beta 1, and rearrangement of the two alleles of C beta 2 when analyzed by Southern blot hybridization. Restriction analysis suggests that the DNA rearrangement is beyond the second joining-region (J) minigene of the J beta 2 cluster. These results establish that at least some mouse suppressor T-cell clones, like helper and cytotoxic T lymphocytes, rearrange and transcribe the genes coding for the alpha and beta chains of the antigen-specific T-cell receptor.